Financial Flexibility: At What Cost? - Garmaise, Mark J.; Natividad, Gabriel (Journal of Financial and Quantitative Analysis, 2021)
Abstract Firms strategically borrow in different locations. Approximately one-quarter of Peruvian companies with operations in multiple areas source their financing from more than one province. Mining windfalls generate finance supply shocks, leading to the provision of more credit at lower average rates, and we show that firms exploit geographic financial flexibility by concentrating their borrowing in booming locations. Firms are less likely to initiate borrowing in new markets when their current borrowing provinces are thriving. The pursuit of flexibility in borrowing markets, however, degrades a firm’s relationships with its existing lenders, thereby heightening its risk of future financial distress.